2014
DOI: 10.2147/dddt.s65349
|View full text |Cite
|
Sign up to set email alerts
|

Virologic breakthrough in a patient with chronic hepatitis B by combination treatment with tenofovir disoproxil fumarate and entecavir

Abstract: Tenofovir disoproxil fumarate (TDF) is widely used to treat hepatitis B virus (HBV) patients in the USA and Europe. No confirmed report of resistance selection during treatment with TDF in treatment-naïve and nucleoside/nucleotide analog-treated chronic hepatitis B patients has yet been reported. Here, we report for the first time a patient with chronic hepatitis B and cirrhosis who emerged with virologic breakthrough during combination therapy with TDF and entecavir (ETV), against ETV-resistant virus. A 51-ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 23 publications
1
14
0
Order By: Relevance
“…However, Suzuki et al . [ 29 ] recently reported the occurrence of virological breakthrough during the long-term follow-up period after TDF plus ETV treatment of patients, suggesting that TDF rescue therapy for drug-resistant patients still need to be closely followed up. The study results, by detecting gene loci, did not show the loci that decreased TDF susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, Suzuki et al . [ 29 ] recently reported the occurrence of virological breakthrough during the long-term follow-up period after TDF plus ETV treatment of patients, suggesting that TDF rescue therapy for drug-resistant patients still need to be closely followed up. The study results, by detecting gene loci, did not show the loci that decreased TDF susceptibility.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is one report of an HIV-and HBVcoinfected patient in whom tenofovir disoproxil fumarate resistance was acquired through the combination of rtL180M and rtM204V, which together confer lamivudine resistance and rtA194T mutations 26) . Suzuki et al 27) also reported a tenofovir-multiple drug resistant strain in a long-term user of NUCs. Our case suggested that it may be important to add tenofovir disoproxil fumarate to entecavir for the patients with multiple drug resistant HBV strain.…”
Section: Discussionmentioning
confidence: 97%
“…Apart from interferon, with the use of NUCs such as entecavir and tenofovir, it is always possible for resistant mutants to emerge [97][98][99][100][101] . Suzuki et al [101] reported that 51-year-old Japanese women with chronic hepatitis B and cirrhosis have virological breakthrough during combination therapy with tenofovir and entecavir against entecavir-resistant virus.…”
Section: Stoppage Of Entecavir or Tenofovirmentioning
confidence: 99%
“…Suzuki et al [101] reported that 51-year-old Japanese women with chronic hepatitis B and cirrhosis have virological breakthrough during combination therapy with tenofovir and entecavir against entecavir-resistant virus. Even long-term therapy with tenofovir against the entecavir-resistant virus has the potential to induce virological breakthrough and resistance.…”
Section: Stoppage Of Entecavir or Tenofovirmentioning
confidence: 99%